A review on Acacia auriculiformis: importance as pulpwood planted in social forestry. (3rd July 2021) - Haque, Md. Moinul; Ni, Yonghao; Akon, A. S. M. Jahir Uddin; Quaiyyum, M. A.; Jahan, M. Sarwar
ABSTRACT: Acacia, an exotic fast-growing tree species was introduced into Southeast Asian countries on degraded soils. In Bangladesh, China, India, Vietnam, Indonesia plantations of Acacia were established for pulpwood production with people's participation. This paper reviews the current knowledge of the physical, chemical and morphological characteristics of A. auriculiformis and its pulping potential. The wood density, chemical and morphological properties of A. auriculiformis impacted positively for pulpwood selection in many countries. A. auriculiformis planted in a social forestry programme in Bangladesh and other countries showed almost similar characteristics to A. auriculiformis grown in different parts of the world. It is a promising species for pulping in Bangladesh and other Southeast Asian countries, at the same time poor people can improve their livelihood through participation in social forestry programme by planting this species.